Prevalence of mammary Paget’s disease in urban China in 2016 - Lu Xu (Nature Portfolio, 2021)
Abstract No national data have been available on descriptive epidemiology of mammary Paget’s disease (MPD) in China. This population-based study aimed to estimate the prevalence of MPD and its pattens by sex, age and area in China. We conducted a population-based study using data in 2016 from China’s Urban Employee Basic Medical Insurance and Urban Resident Basic Medical Insurance, covering approximately 0.43 billion residents. MPD cases were identified based on the diagnostic names and codes in claim data. A total of 825 patients of confirmed diagnosis of MPD were found during the study period. The prevalence of MPD in 2016 was 0.42 per 100,000 population (95% CI 0.19 to 0.73), with marked female predominance. The prevalence rates peaked at 40–59 years and ≥ 80 years in females and males, respectively. The prevalence rates varied among different regions, ranging from 0.06 (95% CI 0.00 to 0.23) in Northeast China to 1.21 (95% CI 0.07 to 3.72) in Northwest China. MPD showed marked female predominance in China. Chinese female patients were much younger, with lower prevalence than that in the United States. Obvious sex difference in the age pattern of MPD prevalence was also observed in China.